Relações entre modalidades de alimentação e hábitos orais de sucção não nutritiva em lactentes atendidos em uma unidade básica de saúde: abordagem fonoaudiológica - Granja, Denise Maria Alves (2012)
Introduction: In the beginning of the nineties, the World Health Organization (WHO) and the United Nations Children s Fund (UNICEF) established the Declaration of Innocent, instituting many measures to promote breastfeeding . Researchers indicate that prematurely stopping breastfeeding is connected to the presence of oral habits such as sucking a pacifier or finger. (Lamounier 2003, Chaves2007). Objective: Describe and relate ways of feeding and oral habits in babies of one to six months who participate in a program of speech pathologic intervention in a basic unit of health in the County of Itapecerica da Serra-SP. 1.Method:Casuistic 19 mothers and their babies were attendant between January 2005 to December 2010. 2.Procedure: The study was done using medical records that had been in systematized forms. The information contained the type of food the infant had and the presence or absence of oral suction in early intervention up to 6 months and 29 days of life. The results were submitted using statistical analysis. Results: In the end of intervention, the majority of babies (89.5%) were breastfeeding. And all (100%) don´t show any who were demonstrating proper oral habits were breastfeeding. Conclusion: There was a significant statistical association between breastfeeding and the lack of habits of oral suction (P=0,012) in the population studied. These results suggest that speech pathologic intervention in approach biopsychic influence the prevalence of breastfeeding in comparison with artificial breastfeeding and the reduction of oral habits of nutritive suction not nutritive in the period